A sensitive, high‐throughput, and eco‐friendly analysis of daidzein and its valine carbamate prodrug in rat plasma by supercritical fluid chromatography with tandem mass spectrometry. Issue 16 (29th July 2018) - Li, Yingchao; Zhang, Xingxing; Bai, Xiaochen; Li, Xiaoting; Jiang, Qikun; Zhang, Tianhong
Abstract: A valine carbamate prodrug of daidzein was synthesized to improve its bioavailability because of the poor solubility and low permeability of daidzein. To evaluate the pharmacokinetic behavior of the prodrug, a sensitive and high‐throughput method was developed and validated for the simultaneous determination of daidzein and its prodrug in rat plasma. The samples were extracted by ethyl acetate and then analyzed by a supercritical fluid chromatography with electrospray ionization tandem mass spectrometry method. The separation was achieved by an ACQUITY UPC 2 ™ BEH 2‐EP column maintained at 40°C using carbon dioxide (≥99.99%) and methanol within 3.0 min by gradient elution. The mass transition ion pairs were m/z 254.8→136.7, 398.0→254.9, and 271.0→91.07 for daidzein, the prodrug, and genistein, respectively. The calibration curves were linear over the concentration ranges of 2–500 ( r  > 0.997) and 10.0–5000.0 ng/mL ( r  > 0.996) with lower limits of quantification of 2 and 10 ng/mL for daidzein and the prodrug, respectively. The intra‐ and interday accuracy and precision were within ±15% for all quality control samples. This developed method enabled high specificity, low cost, low solvent consumption, and a brief analysis time and was successfully applied to a bioavailability evaluation of daidzein and its carbamate prodrug.